(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The article discusses the difficulties of the scientific style of speech that students of non-linguistic universities need to overcome when studying the language of their specialty, and also lists the linguistic features of the scientific style of speech that are worth paying attention to. Russian Russian The author examines the features of the scientific style of the Russian language, wells on the key points that should be taken into account in the preparation of students studying the Russian language.